A micropillar array-based microfluidic chip for label-free separation of circulating tumor cells: The best micropillar geometry? - Mehdi Rahmanian; Omid Sartipzadeh Hematabad; Esfandyar Askari; Farhad Shokati; Atin Bakhshi; Shiva Moghadam; Asiie Olfatbakhsh; Esmat Al Sadat Hashemi; Mohammad Khorsand Ahmadi; Seyed Morteza Naghib; Nidhi Sinha; Jurjen Tel; et al. (Journal of Advanced Research, 2023)
Introduction: The information derived from the number and characteristics of circulating tumor cells (CTCs), is crucial to ensure appropriate cancer treatment monitoring. Currently, diverse microfluidic platforms have been developed for isolating CTCs from blood, but it remains a challenge to develop a low-cost, practical, and efficient strategy. Objectives: This study aimed to isolate CTCs from the blood of cancer patients via introducing a new and efficient micropillar array-based microfluidic chip (MPA-Chip), as well as providing prognostic information and monitoring the treatment efficacy in cancer patients. Methods: We fabricated a microfluidic chip (MPA-Chip) containing arrays of micropillars with different geometries (lozenge, rectangle, circle, and triangle). We conducted numerical simulations to compare velocity and pressure profiles inside the micropillar arrays. Also, we experimentally evaluated the capture efficiency and purity of the geometries using breast and prostate cancer cell lines as well as a blood sample. Moreover, the device’s performance was validated on 12 patients with breast cancer (BC) in different states. Results: The lozenge geometry was selected as the most effective and optimized micropillar design for CTCs isolation, providing high capture efficiency (>85 %), purity (>90 %), and viability (97 %). Furthermore, the lozenge MPA-chip was successfully validated by the detection of CTCs from 12 breast cancer (BC) patients, with non-metastatic (median number of 6 CTCs) and metastatic (median number of 25 CTCs) diseases, showing different prognoses. Also, increasing the chemotherapy period resulted in a decrease in the number of captured CTCs from 23 to 7 for the metastatic patient. The MPA-Chip size was only 0.25 cm2 and the throughput of a single chip was 0.5 ml/h, which can be increased by multiple MPA-Chips in parallel. Conclusion: The lozenge MPA-Chip presented a novel micropillar geometry for on-chip CTC isolation, detection, and staining, and in the future, the possibilities can be extended to the culture of the CTCs.